Oxidative alteration of Trp-214 and Lys-199 in human serum albumin increases binding affinity with phenylbutazone: A combined experimental and computational investigation - Bertozo, Luiza de Carvalho [UNESP]; Tavares Neto, Ernesto [UNESP]; de Oliveira, Leandro Cristante [UNESP]; Ximenes, Valdecir Farias [UNESP] (MDPI, 2018)
Human serum albumin (HSA) is a target for reactive oxygen species (ROS), and alterations of its physiological functions caused by oxidation is a current issue. In this work, the amino-acid residues Trp-214 and Lys-199, which are located at site I of HSA, were experimentally and computationally oxidized, and the effect on the binding constant with phenylbutazone was measured. HSA was submitted to two mild oxidizing reagents, taurine monochloramine (Tau-NHCl) and taurine dibromamine (Tau-NBr2). The oxidation of Trp-214 provoked spectroscopic alterations in the protein which were consistent with the formation of N′-formylkynurenine. It was found that the oxidation of HSA by Tau-NBr2, but not by Tau-NHCl, provoked a significant increase in the association constant with phenylbutazone. The alterations of Trp-214 and Lys-199 were modeled and simulated by changing these residues using the putative oxidation products. Based on the Amber score function, the interaction energy was measured, and it showed that, while native HSA presented an interaction energy of −21.3 kJ/mol, HSA with Trp-214 altered to N′-formylkynurenine resulted in an energy of −28.4 kJ/mol, and HSA with Lys-199 altered to its carbonylated form resulted in an energy of −33.9 kJ/mol. In summary, these experimental and theoretical findings show that oxidative alterations of amino-acid residues at site I of HSA affect its binding efficacy.
Keywords: Albumin; N′-formylkynurenine; Oxidative stress; Phenylbutazone; Taurine dibromamine; Tryptophan